Anthropogenic impact on wetland bird diversity in and around of Budhi and Tengra rivers of Itahari Municipality - Dahal, Sanju; Chhetry, Damodar Thapa (BIBECHANA, 2012)
The diversity and population of birds was studied from January, 2011 to December, 2011, once a week regularly. Altogether fifteen species of wetland birds were recorded from Tengra and Budhi rivers. Maximum species were recorded in January and minimum in July and August. Out of total bird species 40% were migratory, 46.67 % were resident, and 13.33 % were winter visitors. On the basis of abundance, there were 46.67% scarce, 33.33% fairly common and 20% common. On the basis of their population status, maximum number belonged to Ardeola grayii species and minimum in Leptoptilos javanicus species. Maximum species of the birds belonged to family Ardeidae. According to statistical analysis, the resident bird were more diversed then migrant and winter visitor respectively. Similarly, resident birds were much evenly distributed then winter visitors and migrant respectively. The study revealed decreasing trend of bird species from previous period. The conversion of wetland into agricultural land and plotting programmes were the main causes to decline the bird species. DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7184 BIBECHANA 9 (2013) 113-120